2014
DOI: 10.1017/s0022215114002230
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre's syndrome – an unusual complication of otitis externa in a young, healthy female

Abstract: Lemierre's syndrome is a potentially fatal complication associated with significant morbidity. A high index of suspicion is required for prompt recognition and the early institution of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Twenty-four percent of the cases were presented with a complaint in the pharyngeal area (tonsillitis, pharyngitis, common sore throat), whereas a few came with an initial complaint of a swelling of the neck, 37 , 61 , 64 66 , 73 , 82 due to either the thrombus itself or an abscess located in the neck region. Only eleven cases were described with initial difficulties in the dental region, 6 , 16 , 18 , 42 , 46 the otogenic region, 18 , 19 , 68 , 77 or the central nervous system. 29 , 45 Atypical presentations included seizures 90 and blindness.…”
Section: Diagnosismentioning
confidence: 99%
“…Twenty-four percent of the cases were presented with a complaint in the pharyngeal area (tonsillitis, pharyngitis, common sore throat), whereas a few came with an initial complaint of a swelling of the neck, 37 , 61 , 64 66 , 73 , 82 due to either the thrombus itself or an abscess located in the neck region. Only eleven cases were described with initial difficulties in the dental region, 6 , 16 , 18 , 42 , 46 the otogenic region, 18 , 19 , 68 , 77 or the central nervous system. 29 , 45 Atypical presentations included seizures 90 and blindness.…”
Section: Diagnosismentioning
confidence: 99%
“…17 Contrast-enhanced CT is considered the imaging study of choice for this purpose by several authors. 8 , 17 – 21 As with our case, ultrasound offers a rapid, low-cost, noninvasive method of imaging the IJ vein. Ultrasound is limited by its ability to visualize recently formed, unorganized clot and incomplete evaluation of tissue adjacent to the mandible, clavicle, and skull base.…”
Section: Discussionmentioning
confidence: 60%
“…Since many F. necrophorum strains have beta-lactamase activity, most authorities recommend empiric treatment with clindamycin or a beta-lactamase resistant penicillin with good anaerobic coverage such as ticarcillin/clavulanate or ampicillin/sulbactam. 15 , 16 , 21 , 22 The use of anticoagulation is controversial and no controlled studies exist, though more recent retrospective studies have advocated for its use. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Though the radio-isotope scans repeated during this episode and while on follow up would have been conclusive in this regard, unfortunately we couldn’t do it in our case. The other possibility to consider in our case is acute otitis media or acute mastoiditis complicating as thrombosis of sigmoid sinus and IJV thrombosis ( Davidoss et al., 2015 ; Turan et al., 2014 ). However, when the mastoid was explored, the middle ear inflammation was not significant and there was no involvement of the sinus plate.…”
Section: Discussionmentioning
confidence: 99%
“…The IJV thrombosis in MOE by itself has been reported sparsely and very rarely has this been attributed to parapharyngeal space involvement ( Kornilenko et al., 2017 ; Low and Lhu, 2018 ; Kornilenko et al., 2017 ; Davidoss et al., 2015 ; Turan et al., 2014 ). On the other hand, though many authors have reported a non-predictable spread of the MOE to involve non-contagious sites belonging to separate compartments causing VI, VII, IX, X, XI, XII nerve palsies in various combinations very rarely these deficits have been thought to be due to parapharyngeal space involvement.…”
Section: Discussionmentioning
confidence: 99%